Agricultural Economics Society - (:unkn) unknown (My University, 2026)
The Agricultural Economics Society is one of the world's leading associations of professional and academic agricultural economists. Founded in 1926, the AES has some 600 members in 65 countries throughout the world. The Society’s main event is its ANNUAL CONFERENCE held in March/April. This offers an opportunity for students, researchers and established members of the profession to submit papers, debate topical and policy issues and network at a residential, 3-day event. In addition the Society, jointly with Defra (Department for the Environment, Food and Rural Affairs), holds a 1-day event in December each year where the topic is one of current relevance and debate. AES aims to promote the study and teaching of agricultural economics and relevant disciplines, and their application to issues in the agricultural, food and related industries, rural communities and the environment. The relevant disciplines include agriculture, economics, statistics, marketing, business management, politics, food marketing, environmental studies, geography, history and sociology. Members receive the Journal of Agricultural Economics, a leading academic journal in the field, and/or the policy-orientated journal of agri-food and rural resource issues EuroChoices, both of which are available in hard copy. Members also have free access to the online versions.